The awareness of fake news phenomenon through information literacy competency in social networking sites (SNS) / Arlyssa Lim, Wan Ab Kadir Wan Dollah & Safawi Abdul Rahman - Lim, Arlyssa; Wan Dollah, Wan Ab Kadir; Abdul Rahman, Safawi (Universiti Teknologi MARA, 2021)
This study examines the relationship between Information Literacy (IL) competency and fake news phenomenon in Social Networking Sites (SNS). Data for this study has been collected from the Coursework Master level students of Faculty of Information Management (FIM) in UITM Campus Puncak Perdana by using a simple random sampling method with a total sample data of 97 respondents. The data was analyzed using SPSS version 25 and SmartPLS 3.0. The results indicated that the relationship between IL competency and fake news phenomenon in SNS is significant. On the other hand, the findings found that the level of IL competency of Coursework Master level students of FIM in UITM Campus Puncak Perdana is high. Although facing several limitations, this research makes quite a several contributions and this study has provided evidence on the relationship between IL competency and fake news phenomenon in SNS, which suggests that the IL approach will be a great alternative in addressing the fake news phenomenon.